Building chaos : an international comparison of deregulation in the construction industry - Bosch, Gerhard (Routledge studies in business organization and networks ;, 2003)
This collection draws on international comparisons from the main industrialized countries in a key field - the construction industry. One only has to walk around almost any major city in the industrialized economies of the world to see how well the construction industry is doing and this study is a timely analysis of a growing field. This genuinely internationally focused book has contributions from leading experts and academics in the sphere of construction. This well-written, informative collection is a must-read book for advanced students, academics and professionals who are serious a.